7. IMPLEMENTASI KERJASAMA DAERAH KUNCI BERSAMA (KUNINGAN, CIREBON, CIAMIS, CILACAP, BANJAR, BREBES, MAJALENGKA) - Yuwanto Yuwanto (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
Kunci bersama is inter-regional cooperation conducted eight counties and cities that border region, in West Java and Central Java.The cooperation covers many aspects but is currently focused on the improvement of infrastructure such as roads connecting the border between the districts. such cooperation has become one of the main methods to accelerate regional development. This research focuses on how this collaboration process and what programs have been carried out with a qualitative approach. The results of this research indicate that maximum cooperation has not done so already, but there are some programs that accomplished.